The clinical relevance of broad mutational screening of myeloproliferative neoplasms at diagnosis - Pettersson, Helna; Adamsson, Jenni; Johansson, Peter; Nilsson, Staffan; Palmqvist, Lars; Andréasson, Björn; Asp, Julia (Frontiers in Oncology, 2023)
Myeloproliferative neoplasm (MPN) is a heterogenous group of hematological malignancies including polycythemia vera (PV), essential thrombocythemia (ET) and primary myelofibrosis (PMF). JAK2V617F is the most frequent driver mutation in all three entities, but in PMF and ET mutations in CALR and MPL are also frequent. Mutations seen in additional genes are also often the same regardless of subtype of MPN. The aim of this study was to analyze a population based MPN cohort for genetic variants with prognostic value that can guide clinical decisions. MPN patients from Western Sweden diagnosed between 2008-2013 (n=248) were screened for mutations in 54 genes associated with myeloid malignancy. Mutations in the genes SRSF2 and U2AF1 correlated significantly with impaired overall survival but did not correlate to increased risk for vascular events, neither before nor after diagnosis. Rather, mutations in these genes showed an association with disease transformation. Several recurrent gene variants with allele frequency close to 50% were confirmed to be germline. However, none of these variants was found to have an earlier onset of MPN. In conclusion, we identified gene mutations to be independent markers of impaired survival in MPN. This indicates the need for more individualized assessment and treatment of MPN patients and a wider gene mutation screening already at diagnosis. This could ensure the identification of patients with high-risk mutations early on. In addition, several genetic variants were also identified as germline in this study but gave no obvious clinical relevance. To avoid conclusions from non-informative genetic variants, a simultaneous analysis of normal cell DNA from patients at diagnosis should be considered.